New technologies and the demand for heterogeneous labor: Firm-level evidence for the German business-related services sector - Ulrich Kaiser (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
This paper investigates the impact of modern information and communication technologies on the demand for heterogeneous labor. It starts with an interrelated factor demand system. The "desired" level of employment, which is needed in such models, is derived from a generalized Leontief cost function with quasi-fixed factors. Cross-sectional data taken from an innovation survey in the service sector are used in the empirical analysis. The model is estimated by a trivariate ordered probit model. Evidence in favor of skill-biased technological change in the fast growing German business-related services sector is found. The paper suggests a new method of calculating skill- and firm-specific labor cost from information on total labor cost and the share of each skill group in total employment only. It also proposes an approach to calculate long-run elasticities in an ordered probit context.
Keywords: C35; D24; J21; L84; 330; interrelated factor demands; Generalized Leontief cost function; heterogeneous labor demand; business-related services; labor cost decomposition; trivariate ordered probit model